Hoaks dalam Perspektif Hadis: Strategi Penanggulanan dan Pengintegrasian pada Kurikulum Pendidikan Agama Islam - Nasuki, Ahmad (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2023)
Hoax existed long before the advent of technology. The history of Islamic civilization records that hoaxes have existed since the time of the Prophet Adam AS. Even hoaxes have happened to the household of the Prophet Muhammad PBUH. This event is universally enshrined in the Qur'an and narrated in detail in the books of Hadith. Ironically, nowadays, hoaxes have attacked the younger generation of the nation. In this case, Islamic Education teachers need to teach students how to deal with hoaxes. Therefore, this study aims to tackle hoaxes by analyzing the strategies used by the Prophet Muhammad PBUH. and integrate these strategies into the Islamic education curriculum. The formulation of the problem used in this study are: 1. What is the strategy for tackling hoaxes in the perspective of hadith? 2. How to integrate strategies for tackling hoaxes from the hadith perspective into the Islamic Education curriculum?. To answer these two questions, this research uses a qualitative method with the type of library research. This research concludes that the Prophet Muhammad PBUH. using four strategies in tackling hoaxes, namely: discussion strategies, broadening horizons, clarifying and managing emotions. This strategy can be integrated into the Islamic religious education curriculum.